Pendampingan Pembelajaran Al-Qur’an Bagi Para Pedagang Pasar Pengkolan Pasawahan Kidul Kec. Pasawahan Kab. Purwakarta - Dede Kurnia, Asep; Jalaludin, Jalaludin; Novita, Diana (STIE Syariah Indonesia Purwakarta, 2021)
Based on the results of temporary observations, it was found that many Pengkolan Pasawahan Kidul traders who read the Qur'an were still haltingly, the reasons were various, there was a reason that they were busy with their respective trading businesses, so they did not take the time to read the Qur'an. The next reason is because from a young age he was not fluent in reading the Qur'an, because his parents did not pay attention to the education of the Qur'an, until he was carried away until now. The results of community service with the theme of Al-Qur'an Learning Assistance for Traders at the Pasar Pengkolan Pasawahan Purwakarta through several methods and approaches. For traders who are still illiterate in Arabic (hijaiyah), the PKM team uses the Baghdadiyah method, which is also known as the